HUBUNGAN ANTARA PENGETAHUAN IBU TENTANG KEBERSIHAN GENETALIA BALITA DENGAN KEJADIAN INFEKSI SALURAN KEMIH (ISK) PADA BALITA DI POLIKLINIK ANAK MAYAPADA HOSPITAL TANGERANG - Retno Andriati; Ayu Rahayu; Marsondang Situmeang; Dyna Meilolita Sirait; Verawati Simatupang; Nur Hadiyaningsih; Team Perawat OPD 3 (Nusantara Hasana Journal, 2025)
Urinary tract infection (UTI) is one of the most common infectious diseases in childhood. Urinary tract infections can be caused by a variety of microorganisms, such as bacteria, viruses, and fungi, but this infectious disease is more often caused by bacteria. To determine the relationship between maternal knowledge about toddler genital hygiene and the incidence of urinary tract infection (UTI) in toddlers at the Mayapada Hospital Pediatric Clinic in 2023. This study used a cross sectional design, with a sample size of 34 respondents, the instrument used was a questionnaire. Based on the results of the study, poor maternal knowledge about genital hygiene with toddlers diagnosed with UTIs was 9 respondents (26.5%) while good maternal knowledge about genital hygiene with toddlers who were not diagnosed with UTIs was 9 respondents (26.5%). The p-value of 0.011 <0.05 was obtained, which means that there is a relationship between maternal knowledge about genital hygiene of toddlers with the incidence of urinary tract infections (UTI).